Environmental risk assessment of the emerging EDCs contaminants from rural soil and aqueous sources: Analytical and modelling approaches. (May 2018) - Song, Xiaoming; Wen, Yujuan; Wang, Yuanyuan; Adeel, Muhammad; Yang, Yuesuo
Abstract: The emerging endocrine disrupting chemicals posed high risk and much uncertainty to eco-environment and human health. An analytical method, developed for the simultaneous determination of five steroid estrogens in groundwater and soil based upon solid phase extraction and gas chromatography-mass spectrometry, was applied to investigate the distribution of estrone and 17β-estradiol around Shenyang City with particular focus on penetrating from surface to groundwater in this study. Mean concentrations of the estrone and 17β-estradiol were 55.1 ng L −1 and 56.1 ng L −1 in groundwater, 32.5 ng g −1 and 23.1 ng g −1 in soil, respectively. The distribution of estrone and 17β-estradiol were similar in groundwater, the concentration in the west of the site center was relatively low, and the surroundings were relatively high. The concentration of estrone was changed less, but 17β-estradiol was significantly increased in silt and silty sand layers in vadose zone profiles. Both estrone and 17β-estradiol concentrations changed abruptly at the interface of layers. Incorporating the temporal and spatial evolution of physical-chemical-biological environmental parameters at the sites, sorption and biodegradation were suggested the controlling roles in the fate and transport of SEs in the soil-groundwater system. The Ecological risk quotients values of both soil and groundwater indicated a very high ecological risk associated with SEs, but the non-carcinogenic harm quotients did not exceed the acceptable level of non-carcinogenic human health risk. Highlights: A sensitive and selective analytical method for SEs has been developed based on ULE/SPE-GC/MS. E1 and 17β-E2 were detected and distributed as a similar pattern in groundwater in the suburban farm. The concentrations of SEs changed abruptly at the stratigraphic interface in vadose zone. Higher ecological risk of SEs was identified in groundwater compared to the soil in this rural farm. The estrogenic health risk was determined low under different exposure pathways.